Directional Three-Dimensional Macroporous Carbon Foams Decorated with WC1−x Nanoparticles Derived from Salting-Out Protein Assemblies for Highly Effective Electromagnetic Absorption - Chen, Yongzheng; Gai, Lixue; Hu, Bo; Wang, Yan; Chen, Yanyi; Han, Xijiang; Xu, Ping; Du, Yunchen (Nano-Micro Letters, 2025)
Directional three-dimensional carbon-based foams are emerging as highly attractive candidates for promising electromagnetic wave absorbing materials (EWAMs) thanks to their unique architecture, but their construction usually involves complex procedures and extremely depends on unidirectional freezing technique. Herein, we propose a groundbreaking approach that leverages the assemblies of salting-out protein induced by ammonium metatungstate (AM) as the precursor, and then acquire directional three-dimensional carbon-based foams through simple pyrolysis. The electrostatic interaction between AM and protein ensures well dispersion of WC1−x nanoparticles on carbon frameworks. The content of WC1−x nanoparticles can be rationally regulated by AM dosage, and it also affects the electromagnetic (EM) properties of final carbon-based foams. The optimized foam exhibits exceptional EM absorption performance, achieving a remarkable minimum reflection loss of − 72.0 dB and an effective absorption bandwidth of 6.3 GHz when EM wave propagates parallel to the directional pores. Such performance benefits from the synergistic effects of macroporous architecture and compositional design. Although there is a directional dependence of EM absorption, radar stealth simulation demonstrates that these foams can still promise considerable reduction in radar cross section with the change of incident angle. Moreover, COMSOL simulation further identifies their good performance in preventing EM interference among different electronic components. Highlights: 1 A groundbreaking approach is developed for the fabrication of directional macroporous WC1−x/C foams, which frees the dependence on unidirectional freezing technique from the construction of directional macroporous carbon-based composites. 2 The electrostatic interaction between ammonium metatungstate and protein makes in situ generated tungsten carbide (WC1−x) nanoparticles well disperse on carbon flakes. 3 The optimized foam exhibits exceptional electromagnetic absorption performance, achieving a remarkable minimum reflection loss of − 72.0 dB and an effective absorption bandwidth of 6.3 GHz.